Rigorous idiography: Exploring subjective and idiographic data with rigorous methods—The method of derangements - Evans, Chris; Carlyle, Jo-anne; Paz, Clara (Frontiers in Psychology, 2023)
One unavoidable issue limiting psychological research into the subjective is a wish to have general rules, or at least statistical regularities applying across individuals, ideally to all people. This is intrinsically in tension with all that is unique to any individual. There are statistical regularities across individuals’ purely subjective self-report and much psychology and psychotherapy research is based on data from self-report questionnaire responses: subjective data. The statistical and psychometric methods that help explore such data are a fundamental part of Cronbach & Meehl’s (1955) foundational nomological networks of validity. This paper summarises routine psychometric methods that explore nomothetic subjective data. We then recapitulate the method and logic of one remarkably simple test that purely idiosyncratic data can convey valid information. We also explore how the method appeared to become stuck in a bibliometric backwater and hope it will be taken up and used correctly and more widely.